Ultra-Fast and High-Reliability SOT-MRAM: From Cache Replacement to Normally-Off Computing - Prenat, Guillaume; Garello, Kevin; Langer, Juergen; Ocker, Berthold; Cyrille, Marie-Claire; Gambardella, Pietro; Tahoori, Mehdi; Gaudin, Gilles; Jabeur, Kotb; Vanhauwaert, Pierre; Pendina, Gregory Di; Oboril, Fabian; et al. (IEEE transactions on multi-scale computing systems, 2016)
This paper deals with a new MRAM technology whose writing scheme relies on the Spin Orbit Torque (SOT). Compared to Spin Transfer Torque (STT) MRAM, it offers a very fast switching, a quasi-infinite endurance and improves the reliability by solving the issue of "read disturb", thanks to separate reading and writing paths. These properties allow introducing SOT at all-levels of the memory hierarchy of systems and adressing applications which could not be easily implemented by STT-MRAM. We present this emerging technology and a full design framework, allowing to design and simulate hybrid CMOS/SOT complex circuits at any level of abstraction, from device to system. The results obtained are very promising and show that this technology leads to a reduced power consumption of circuits without notable penalty in terms of performance.